Legal Protection for Wives in Unregistered Polygamous Marriages: An Analysis of Islamic Law in Indonesia - Asrat Nita Wati; Pagar Pagar; Hasan Matsum (Faculty of Law, Universitas Pekalongan, 2025)
Indonesia’s Marriage Law No. 16/2019 mandates marriage registration, yet cultural-religious norms perpetuate nikah sirri (unregistered marriages), particularly in polygamy, denying wives spousal rights. While Islamic law validates such unions via rukun and syarat, statutory exclusion strips wives of inheritance, alimony, and child legitimacy, violating maqashid sharia principles like hifz al-nasl (lineage) and hifz al-mal (property). Prior studies identify this dissonance but lack systemic reforms bridging Islamic jurisprudence and comparative law. This research addresses this gap by analyzing wives' legal status in unregistered polygamy under Islamic and Indonesian law, designing reforms reconciling religious validity with enforceable safeguards. Using normative legal research, it combines doctrinal analysis of Islamic texts/statutes with qualitative analysis of Religious Court rulings. Findings reveal 78% of nikah sirri wives face economic disenfranchisement, and 89% lack alimony recourse due to burdensome retroactive marriage validation. Comparatively, Malaysia’s and Morocco’s laws slashed polygamy rates (95%, 99.7%) via judicial oversight absent in Indonesia. Legal pluralism enables patriarchal qiwamah interpretations: 67% of Java’s polygamy permits bypass spousal consent; 72% of rural nikah sirri involve child brides. Consequently, 81% of unregistered wives suffer disinheritance; 54% of children endure stigma. The study innovates by proposing a hybrid reform model integrating maqashid sharia with feminist jurisprudence, advocating specialized courts, simpler isbat nikah, and criminalizing unregistered solemnization. Aligning with Moroccan/Malaysian models could cut nikah sirri by 40%, upholding hifz al-ird (dignity) and constitutional equity, offering a blueprint for Muslim-majority nations